2022
DOI: 10.3390/s22093567
|View full text |Cite
|
Sign up to set email alerts
|

Gender and Age Differences in Preferences on Game Elements and Platforms

Abstract: This paper analyzes different player type models and game elements in the literature, particularly focusing on the case of online games. Research based on an exploratory study is presented; it aims to explore the different types of interaction with gameful digital applications. The study is based on a survey and provides findings from the literature review and empirical insights about users’ differences and preferences regarding game elements. The results reveal demographics regarding player profiles and the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Based on the literature, existing frameworks or models in the field of serious educational games have not taken into account the preferences of players, while paying attention to the interests of users can be very helpful in attracting them to the game [ 26 , 61 ]. Accordingly, González et al discovered gender and age differences in preferences for device or platform type and game elements [ 62 ]. Moreover, Manero et al indicated that gaming preferences can influence the effectiveness of learning approaches [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the literature, existing frameworks or models in the field of serious educational games have not taken into account the preferences of players, while paying attention to the interests of users can be very helpful in attracting them to the game [ 26 , 61 ]. Accordingly, González et al discovered gender and age differences in preferences for device or platform type and game elements [ 62 ]. Moreover, Manero et al indicated that gaming preferences can influence the effectiveness of learning approaches [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Throughout the years, researchers have worked on how certain characteristics may affect the users while using a gamified system, and therefore, how people could be grouped into different profiles according to these characteristics and motivations 14 – 16 . Players and users typologies are used to try to simplify the complexity of the users 17 , 18 , and the choice of the user typology is one of the main factors that can influence the user motivation in personalized gamified environments 13 . The Hexad, a user model introduced by Marczewski 19 , is shown to be the only empirically validated (albeit partially) 20 created exclusively for gamification.…”
Section: Introductionmentioning
confidence: 99%